2021
DOI: 10.1175/wcas-d-20-0132.1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Disasters in Northeast Brazil: Hydrometeorological, Social and Sanitary Factors

Abstract: The occurrence of environmental disasters affects different social segments, impacting health, education, housing, economy and the provision of basic services. Thus, the objective of this study was to estimate the relationship between the occurrence of disasters and extreme climate, sociosanitary and demographic conditions in the Northeast region of Brazil during the period from 1993 to 2013. Initially, we analyzed the spatial pattern of the incidence of events and, subsequently, generalized additive models fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…Many studies have identified a gradual increase in temperature and changes in rainfall patterns across multiple Brazilian regions, accompanied by an increase in the frequency and intensity of extreme weather events (Marengo and Bernasconi, 2015;Ávila et al, 2016;Lyra et al, 2017;Oliveira et al, 2017;Zilli et al, 2017;Fernandes and Rodrigues, 2018;Bezerra et al, 2019;Da Silva et al, 2019;Avila-Diaz et al, 2020;Dunn et al, 2020;Rodrigues et al, 2020Rodrigues et al, , 2021Costa et al, 2021). Moreover, most climateinduced disasters in Brazil are associated with extreme rainfall events (CEPED, 2013c;Rodrigues et al, 2020;Ribeiro et al, 2021;Palharini et al, 2022), and the consequences of these events are highly dependent on the vulnerability and response capacity of affected areas.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have identified a gradual increase in temperature and changes in rainfall patterns across multiple Brazilian regions, accompanied by an increase in the frequency and intensity of extreme weather events (Marengo and Bernasconi, 2015;Ávila et al, 2016;Lyra et al, 2017;Oliveira et al, 2017;Zilli et al, 2017;Fernandes and Rodrigues, 2018;Bezerra et al, 2019;Da Silva et al, 2019;Avila-Diaz et al, 2020;Dunn et al, 2020;Rodrigues et al, 2020Rodrigues et al, , 2021Costa et al, 2021). Moreover, most climateinduced disasters in Brazil are associated with extreme rainfall events (CEPED, 2013c;Rodrigues et al, 2020;Ribeiro et al, 2021;Palharini et al, 2022), and the consequences of these events are highly dependent on the vulnerability and response capacity of affected areas.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of a disaster event are effects on society, the environment, geology, social vulnerability, economic vulnerability, psychological effects and inadequate response capacity (Chmutina and von Meding, 2019;UNODRR, 2020). These events involve natural and social processes that affect society according to the patterns of interaction between disaster events and social organizations (Ribeiro et al, 2021). Environmental disasters such as disease cycles will also result in major economic losses and negatively affect the provision of essential services.…”
Section: Introductionmentioning
confidence: 99%